PENGARUH PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) TERHADAP KEMAMPUAN BERPIKIR ANALISIS SISWA PADA MATERI PENCEMARAN LINGKUNGAN - Suryanda, Ade; Azrai, Eka Putri; Wari, Nares (Biosfer: Jurnal Pendidikan Biologi, 2018)
The analytical thinking skill is a part of the higher order thinking process. The analytical thinking skill is needed to solve a problem in learning process. The analytical thinking has 5 process, there are matching, classifying, analyzing errors, generalizing, and specifying. Group Investigation (GI) model is applied in learning to improve the analytical thinking skill of students in environmental pollution. This research aimed to determine the influence of applying Group Investigation (GI) model on student analytical thinking skill in environmental pollution. This research was held on second semester of academic year 2015/2016 on April until May 2016 in Labschool Kebayoran Junior High School. The kind of this research is a quantitative research with quasi experiment methods. The subject of this research is students in Class VII-B and VII-F Labschool Kebayoran Junior High School. The instrument which used are essay post-test with 15 questions and carried out-learning observations sheet. Based on the result of research, obtained the mean of the analytical thinking skills score test in experiment class is higher than control class, that is 78,46 > 69,43. The prerequisite test shows that data normally distributed and class groups derived from a homogenous population. The hypothesis test uses t-test on 0,05 significant level shows that there is an influence of applying Group Investigation (GI) model on student analytical thinking skill in environmental pollution.